Fatores motivadores para a adoção de Internet das Coisas: a perspectiva de especialistas em IOT - Rocha, Klayton Eduardo da (2019)
The Fourth Industrial Revolution is characterized by the set of technological innovations contemporaries to the development of this work, such as artificial intelligence, advanced robotics, impressions in three dimensions, internet of things, among others. An initial review of the internet of things literature has shown that this technology has the potential to dramatically change companies and their operations, but there are many associated challenges, such as choosing which technologies are best suited and in which operations your applications can bring the most return. Thus, given these challenges, this study aims to present a framework that characterizes and identifies the drivers that influence the adoption of the internet of things. Identifying and understanding the motivations associated with the adoption of internet of things can help to discuss the benefits and difficulties associated with using this technology in different business operations. The initial review of the literature did not identify studies that presented the drivers for the adoption of the internet of things, thus, a review was made about the drivers of technology adoption. This step resulted in the development of a questionnaire that guided the empirical identification of drivers of internet of things adoption. All questions identified in the literature were normalized in a questionnaire, by eliminating repetitions, simplifying texts and centralizing concepts to the internet of things. This process was evaluated by three technical consultants in the areas of project evaluation, digital innovation and impact assessment, generating a final document with questions grouped into eight drivers: planning, finance, talent, technology, outsourcing, competitors, government and society. The Delphi method was used for a panel development with experts sharing their experiences related to six internet of things adoption projects. The planning driver was observed to be of high importance for internet of things adoption based on panelists' speeches on collaboration, innovation and process optimization. The talent driver was observed to be of high importance when experts evaluated the impact of internet of things adoption and people development. However, the technology driver presented itself as a barrier to internet of things adoption from the panelists' perspective when discussing the need for scalability of projects, as well as the governance factor also presented as a barrier, as five of the six panels studied indicated a lack of government incentives for internet of things adoption. The application of the questionnaire to companies from other sectors and geographies, as well as quantitative study methods (e.g. survey) are suggested as opportunities for future work.